Prevalence of depression, anxiety, fatigue, and headache before and after long COVID onset : a case-control study in the total population of Region Stockholm - Lindblom, Sebastian; Lindberg, Pia; Ljunggren, Gunnar; Lee, Seika; Kisiel, Marta A; Kolosenko, Iryna; Petrovic, Predrag; Sklivanioti Greenfield, Myrto; Wachtler, Caroline; Fedorowski, Artur ; 0000-0002-5352-6327; Wheelock, Åsa M; Carlsson, Axel C (BMC Medicine, 2025)
BACKGROUND: Post-acute sequelae of SARS-CoV-2 infection, or long COVID, include diverse symptoms and remain a major concern worldwide. This study investigates the occurrence of depression, anxiety, fatigue, and headache 1 year prior to the COVID-19 pandemic (2019), 12 months prior to, and 6 months after long COVID diagnosis in individuals diagnosed with long COVID and matched population-based controls. METHODS: This case-control study included nonhospitalized individuals diagnosed with long COVID compared with controls without long COVID, matched by age, sex, and neighborhood socioeconomic status. Data were collected from the Stockholm Regional Health Care Data Warehouse (VAL), including diagnoses in 2019, 12 months before, and 6 months after the long COVID diagnosis. Conditional logistic regression was used to calculate odds (OR) ratios and 99% confidence intervals (CI). RESULTS: A total of 5589 cases (mean age: 47 years, 69% female) and 47,561 controls were included. Individuals with long COVID had a higher pre-pandemic frequency of the following diagnoses: depression (women: OR 1.57 (1.26-1.97), men: OR 1.40 (0.88-2.23)), anxiety (women: OR 1.65 (1.41-1.93), men: OR 2.10 (1.56-2.84)), fatigue syndrome after viral infection (women: OR 1.96 (0.86-4.48), men: OR 2.22 (0.29-17)), and headache (women: OR 2.45 (1.96-3.05), men: OR 2.89 (1.86-4.50)). Individuals with long COVID also had a higher frequency of these diagnoses 12 months before and 6 months after the long COVID diagnosis was made, regardless of sex. CONCLUSIONS: Individuals with long COVID had a higher prevalence of depression, anxiety, fatigue, and headache both before and after being diagnosed with long COVID compared with controls without long COVID. The findings suggest an association between mental health vulnerabilities and long COVID, while the frequency of registered mental health diagnoses remained largely similar after the long COVID diagnosis.
© 2025. The Author(s).
Keywords: Humans; Male; Female; Sweden/epidemiology; COVID-19/epidemiology; Fatigue/epidemiology; Headache/epidemiology; Case-Control Studies; Middle Aged; Anxiety/epidemiology; Depression/epidemiology; Prevalence; Adult; Aged; Post-Acute COVID-19 Syndrome; SARS-CoV-2